PDMS-PMHS coated optical fiber sensor for detection of ethyl acetate - Per, Junwei (2016)
In recent years, polymers have progressively being applied as potential waveguide materials. This can be traced back to the advantages they have, like possessing excellent biocompatibility, good mechanical and optical properties, and the ease of structure modification.